Construction partnering: moving towards the rationalisation for a dominant paradigm - Lee, Crompton; Goulding, Jack Steven; Rahimian, Farzad Pour (Faculty of Design & Architecture, Universiti Putra Malaysia, 2014)
This paper critically reviews seminal literature on ‘traditional’ and nonmarket partnering exchanges, in order to identify core congruent issues, drivers and agents of change. It draws out a number of key themes to better understand why the construction industry has remained relatively unchanged; even though successive reports have tried to rectify the industry’s challenges. Acknowledging that there is no one clear definition, strategy or template for the effective implementation of partnering, findings from extant literature highlight eight dominant drivers deemed integral to augmenting project performance and profitability. So, whilst the construction industry invariably conducts its business with a smaller ratio of strategic partnerships than commonly believed, and accepting buyer dominance has predominantly remained, it is advocated that there is an exigent need to disentangle the project partnering initiative through some form of deterministic model. The case for this is presented through a relationship schema that maps the fabric, reliance and drivers for partnering success.